Crowdsourced Politics The Rise of Online Petitions & Micro-Donations - Vromen, Ariadne; Halpin, Darren; Vaughan, Michael (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
"Crowdsourced Politics provides a clear-eyed, accessible, and very needed analysis of one of the most important civic and political phenomenons of the twenty-first century: crowd-based online mobilization. We've all seen it but few can understand it or help us make sense of it in the way this book does." -Hahrie Han, Stavros Niarchos Foundation Professor of Political Science, Director of the SNF Agora Institute, Johns Hopkins University "The crowdsourcing of politics - whether it be e-petitions or micro-donations - has become a key area of action, contestation, and debate, impacting how politics and civic life operates. Discussions veer from outright hype to dystopian doom, indifference and disdain. Written by leading scholars in the field, this book cuts through unhelpful dichotomies by analysing what is happening, how and to what effect." -Scott Wright, Professor of Political Communication and Journalism, Faculty of Media & Communication, Bournemouth University This book focuses on online petitioning and crowdfunding platforms to demonstrate the everyday impact that digital communications have had on contemporary citizen participation. It argues that crowdsourced participation has become normalised and institutionalised into the repertoires of citizens and their organisations. To illustrate their arguments the authors use an original survey on acts of political engagement, undertaken with Australian citizens. Through detailed interviews and online analysis they show how advocacy organisations now use online petitions for strategic interventions and mobilisation. They also analyse the policy issues that mobilise citizens on crowdsourcing platforms, including a unique dataset of 17,000 petitions from the popular non-government platform, Change.org. Contrasting mass public concerns with the policy agenda of the government of the day shows there is a disjuncture and lack of responsiveness to crowdsourced citizen expression. Ultimately the book explores the long-term implications of citizen-led change for democracy. Ariadne Vromen is Professor of Public Administration at the Australian National University. Darren Halpin is Professor of Political Science at the Australian National University. Michael Vaughan is post-doctoral researcher at the Weizenbaum Institute for the Networked Society, Freie University Berlin. .
Chapter 1: Why do online crowds matter for contemporary citizen politics? -- Chapter 2: Who signs and shares petitions and donates money online? -- Chapter 3: How do political organisations use online petitioning and crowdfunding? -- Chapter 4: What kinds of issues do citizens successfully raise via online petitions? -- Chapter 5: Why do personal narratives and stories matter for online political engagement? -- Chapter 6: Does online citizen engagement matter for reinvigorating contemporary politics? .
Keywords: Communication in politics; Social justice; Digital media; Technology-Sociological aspects; Information technology; Political Communication; Social Justice; Digital and New Media; Information and Communication Technologies (ICT).